The Description Of Sgot and Sgpt Levels In Hepatitis B Patients at Karsa Husada Hospital Batu Malang - Dhini Larasati; Previta Zeizar Rahmawati (PROFESSIONAL HEALTH JOURNAL, 2026)
Background: Hepatitis B is a liver infection caused by the hepatitis B virus that can lead to hepatocellular damage. Liver enzyme tests, namely Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT), are used as important indicators in assessing the degree of liver damage. Objective: This study aimed to describe the levels of SGOT and SGPT in hepatitis B patients at Karsa Husada Hospital, Batu Malang, during the period of January–December 2024. Methods: This research employed a quantitative descriptive method using secondary data from medical records of 39 patients. Data analysis was conducted using univariate and bivariate approaches. Results: The results showed that elevated SGOT levels were found in 35 patients (89.7%), while normal levels were observed in 4 patients (10.3%). Elevated SGPT levels were observed in 27 patients (69.2%), while 12 patients (30.8%) had normal levels. Based on sex, elevated SGOT levels were more prevalent in males (23 patients, 95.8%) compared to females (12 patients, 80.0%), while elevated SGPT levels were also dominant in males (20 patients, 83.3%) compared to females (7 patients, 46.7%). Based on age groups, the highest elevated SGOT levels were found in adults (22 patients, 91.7%), followed by adolescents (7 patients, 87.5%) and elderly (6 patients, 85.7%). Correlation test results showed a coefficient value of r = 0.380 with p = 0.017 (p < 0.05). Conclusion: These findings indicate that the majority of hepatitis B patients experienced elevated SGOT and SGPT levels, with predominance among adult males, and there was a significant correlation between the two liver enzymes.